GRK Mediates μ-Opioid Receptor Plasma Membrane Reorganization - Gondin, Arisbel B.; Halls, Michelle L.; Canals, Meritxell; Briddon, Stephen J. (Frontiers in Molecular Neuroscience, 2019)
Differential regulation of the μ-opioid receptor (MOP) has been linked to the development of opioid tolerance and dependence which both limit the clinical use of opioid analgesics. At a cellular level, MOP regulation occurs via receptor phosphorylation, desensitization, plasma membrane redistribution and internalization. Here, we used fluorescence correlation spectroscopy (FCS) and fluorescence recovery after photobleaching (FRAP) to detect and quantify ligand-dependent changes in the plasma membrane organization of MOP expressed in human embryonic kidney (HEK293) cells. The low internalizing agonist morphine and the antagonist naloxone did not alter constitutive MOP plasma membrane organization. In contrast, the internalizing agonist DAMGO changed MOP plasma membrane organization in a pertussis toxin-insensitive manner and by two mechanisms. Firstly, it slowed MOP diffusion in a manner that was independent of internalization but dependent on GRK2/3. Secondly, DAMGO reduced the surface receptor number and the proportion of mobile receptors, and increased receptor clustering in a manner that was dependent on clathrin-mediated endocytosis. Overall, these results suggest the existence of distinct sequential MOP reorganization events at the plasma membrane and provide insights into the specific protein interactions that control MOP plasma membrane organization.